Tracing the Physical Identity of Pasuruan City a Study of The Influence of Social Segregation During the Colonial Period - Wijaya, Suryadi Rokhman; Wikantiyoso, Respati; Wahjutami, Erlina Laksmiani (Proceedings of International Conference of Graduate School on Sustainability, 2025)
The city’s architectural performance is greatly influenced by economic, socio-cultural, and political development factors throughout its formation. The prolonged period of Dutch colonial occupation has significantly altered the social order of society. The policy of social segregation of society through ethnic and racial groupings in the city area has implications for the performance of the area’s architecture. The long history of colonialism in Pasuruan has left physical traces of architecture that play a significant role in shaping the character and physical identity of Pasuruan. In 1903, the flow of the Gembong River became a physical separator for the settlements of indigenous and non-indigenous ethnic groups (Europeans, Arabs). This policy has implications for the physical spatial arrangement and architecture of cities. A social segregation study on the character of Pasuruan City was conducted by tracing physical traces, observation, and reviewing related literature/research. The findings of this study are important for mapping the characteristics of the city area, as well as material for the basis of its preservation policy. The results of this study are expected to be in the form of regional development strategies, with suggestions on what city elements need to be maintained to achieve the image of a City area identity.